Transcatheter Arterial Embolization for the Control of Neoplastic Hemorrhage in Locally Advanced Breast Cancer: A Case Report - Ji Hwan Kang; Myung Sub Kim; Hyun Pyo Hong; Do Yeon Ahn (Journal of the Korean Society of Radiology)
Intractable bleeding from locally advanced breast carcinoma is a rare but challenging clinical problem. Given the patients’ poor overall condition and palliative care status, management options are often limited. Transcatheter arterial embolization (TAE) emerges as a potential alternative to traditional surgical or radiation-based approaches for hemorrhage control. This case report presents a successful application of TAE in managing spontaneous bleeding from a locally advanced breast cancer.